2014
DOI: 10.11648/j.ajbio.20140206.14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestibility of Dockounou, a Traditional Plantain Derivate Dish of C?te d’Ivoire

Abstract: The aim of this study was to identify sugar products from dockounou digestion. Tests of digestibility on various dockounou using a digestive juice of young snails namly Archachatina ventricosa and experimental acid hydrolysis were used. The results had showed that boiled dockounou were more hydrolysis than the backed one. Specifically, the rice boiled dockounou was more hydrolyzed than the maize boiled dockounou. Both rice boiled an baked dockounou are more hydrolyzed than the maize dockounou did. The sugars l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In order to contribute to the development of plantain by reducing post-harvest losses due to the non-use of this product at the senescent stage, research is underway to improve traditional products based on it. Thus Akoa et al [11] improved the sensory characteristics of dockounou, a traditional dish made from senescent plantain. According to these authors this dish can be considered as an interesting solution, apt to contribute to the reduction of post-harvest losses and food security.…”
Section: Introductionmentioning
confidence: 99%
“…In order to contribute to the development of plantain by reducing post-harvest losses due to the non-use of this product at the senescent stage, research is underway to improve traditional products based on it. Thus Akoa et al [11] improved the sensory characteristics of dockounou, a traditional dish made from senescent plantain. According to these authors this dish can be considered as an interesting solution, apt to contribute to the reduction of post-harvest losses and food security.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate their probiotic properties, 40 bacterial strains were isolated from fermented Dockounou paste [11]. The LAB isolates were preliminarily identified using conventional techniques, including colonial morphology, Gram staining, and biochemical reactions (catalase and oxidase tests).…”
Section: Lab Strains and Growth Conditionsmentioning
confidence: 99%
“…In recent years, numerous studies have been conducted with a focus on the isolation of LABs and yeasts from traditional fermented foods to identify potential starter cultures that can also exhibit valuable probiotic properties [3][4][5][6]. LAB species have been identified as the agents responsible for the manufacture of various Ivorian indigenous foods and beverages, such as attiéké, attoupkou, placali (fermented tubers), baca, wômi, doklu (fermented cereal-based foods), adjuevan (fermented fish), bandji and tchapalo (fermented beverages), and dockounou (fermented over-ripe fruits of plantain) [8][9][10][11][12][13][14]. Throughout the fermentation process of dockounou paste, Kouadio et al [11] found different types of microorganisms predominating, such as yeasts, bacilli, and lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation